﻿Is radius bone mineral density helpful for fracture risk assessment? - Biver, Emmanuel (Osteologie, 2019)
Although peripheral DXA is not recommended for the diagnosis of osteoporosis or to monitor osteoporotic treatments, its use for fracture risk assessment is supported by several studies. In addition, its potential interest is supported by the recent demonstration, in prospective cohorts, of the contribution of distal radius microstructure and strength, assessed by high-resolution peripheral QCT (HRpQCT), to predict incident fractures beyond the classical clinical tools (femoral neck BMD and FRAX). Indeed, areal BMD measured by DXA at the ultra-distal radius is highly correlated with bone strength derived from HRpQCT measurements at the same site. Ultra-distal radius areal BMD is therefore highly associated with fracture risk, with associations of higher magnitude than at the “classically recommended” one-third distal radius. Furthermore, ultra-distal radius areal BMD is also associated with incident fractures in non-osteoporotic women in women with T-score > –2.5 SD on hip and spine DXA or women with FRAX score below the intervention threshold for age. Since more than half of low-trauma fractures occur in individuals not identified as being at high risk by BMD testing at the spine or hip, radius bone mineral density may help to refine fracture risk in patients with osteopenia defined by central DXA (spine or hip), or relatively few clinical risk factors.
Keywords: fracture risk; bone mineral density; DXA; radius